Information Needs and Source Information of Agricultural Extension Workers in DIY - Retno Wulandari (Universitas Muhammadiyah Yogyakarta, 2015)
One of the important factors that contribute to agricultural development is information. As such agricultural extension workers that link agricultural agencies to the farmers must have adequate and up-to-date information about agricultural practices before they could inform, educate and train the farmers in method and techniques of farming. This study aims to determine the types of information needed by agricultural extension workers; to determine the sources of information used by the agricultural extension workers; and to determine the comparison between types of information with information sources used by agricultural extension workers. The present study was a descriptive study using a survey design and conducted at Daerah Istimewa Yogyakarta (DIY) Province. The populations of the study consists 181 agricultural extension workers divisible in the district level, namely Sleman, Kulon Progo, Gunung Kidul dan Bantul. Sampling procedure in this study used cluster sampling. The method for gathering data from the respondents is based on a structured questionnaire. Descriptive statistics was to describe the characteristics of the respondents and the dependent variables of the study. As a result, most of agricultural extension workers strongly needed the innovation information in seeking information followed by extension service information and extension role information. The result of information sources used by agricultural extension worker for extension service information, innovation information and extension role information indicates that agricultural extension workers used interpersonal source. Most of them never sought information use Internet, they use radio more frequently than television and video, agricultural extension worker also used mass media as information source.